Programming with Microsoft Visual 4.0 for Windows - Zak, Diane (Course Technology, Boston, Mass., 1997)
Aimed at students planning and creating their own interactive Windows applications using the object-oriented programming language, Visual Basic, this text offers task-driven tutorials. Realistic case scenarios provide motivation in step-by-step lessons for both beginners and advanced programmers.
Keywords: Visual Basic 4; Programming